DETERMINANTS OF HOUSEHOLD CHOICE BETWEEN FRESH AND PROCESSED CITRUS FRUITS IN ABEOKUTA SOUTH LOCAL GOVERNMENT AREA, OGUN STATE, NIGERIA - Samuel, H. F.; Tolorunju, E. T.; Awolope, T. M.; Kedo, O. G. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
The study investigated the determinants of household choices between fresh and processed citrus fruits in Abeokuta South Local Government Area, Ogun State, Nigeria. A two-stage sampling technique was used to select 150 respondents, and data were collected using a structured questionnaire. Descriptive statistics and inferential statistics such as binary logistic regression was used to analyse the collected data. Result showed that 55.33% of respondents were female, with a mean age of 33 years; 60.67% were unmarried, the average household size was 5, the mean years of education was 15, and 36% earned above 130,000 Naira. The most consumed fresh citrus fruits were orange (99.33%) and tangerine (82.67%), while the most consumed processed citrus products were packaged orange juice (83.33%) and citrus flavoured drinks (72.67%). Likert scale showed that households were more aware of citrus ability to prevent constipation (mean = 4.14), followed by being a rich source of vitamin C (mean = 3.99). Binary logistic regression indicated that household size (OR = 2.238, p = 0.075), education (OR = 0.601, p = 0.076), expenditure on processed citrus (OR = 1.008, p = 0.003), and family background habits (OR = 0.339, p = 0.049) were significant determinants of household choices between fresh and processed citrus fruits. The study concludes that household choices between fresh and processed citrus fruits are mainly determined by socio-economic factors, especially household size and expenditure. Based on these findings, the study recommends promoting nutritional education and encouraging affordable consumption of citrus products to support healthier household choices.